SAT0226 MINOR SALIVARY GLAND BIOPSY TO DIAGNOSE LYMPHOMA IN PATIENTS WITH PRIMARY SJÖGREN'S SYNDROME. (2nd June 2020) - Parreau, S.; Seror, R.; Terrier, B.; Burroni, B.; Jamart, C.; Régent, A.; Nocturne, G.; Mouthon, L.; Mariette, X.; Le Guern, V.
Abstract : Background: Non-Hodgkin B-cell lymphoma (NHL), especially mucosa-associated lymphoid tissue (MALT) lymphoma, is one of the main complications of primary Sjögren's syndrome (pSS). Frequent extranodal lymphoproliferation makes its diagnosis challenging and obtaining a biopsy difficult. Since pSS-associated lymphomas are very frequently MALT lymphomas with salivary gland involvement, we hypothesized that minor salivary gland biopsy (MSGB) could be useful for NHL diagnosis in this context. Objectives: To evaluate the potential contribution of MSGB for the diagnosis of pSS-associated MALT lymphoma by comparing patients diagnosed with NHL based on MSGB or another tissue. Methods: All pSS patients (ACR/EULAR 2016 classification criteria), from the Paris National Referral Centers for Rare Systemic Autoimmune Diseases, diagnosed with NHL between January 2010 and October 2019, were included. Each patient's clinical, biological, radiological and therapeutic information was collected retrospectively at NHL diagnosis and 1-year later. Only patients with MSGB available were analyzed; they were divided into 2 groups according to MSGB results for NHL: MSGB + and MSGB – . Results: Among 36 pSS patients diagnosed with NHL during the study period, 25 had an MSGB available at the time of NHL diagnosis. Among them, 13 MSGBs contained NHL (MSGB + ). MSGB was the only site enabling NHL diagnosis for 10/13 (77%); pSS and NHL were diagnosed simultaneously in 4/13 (31%). MSBGs were NHL – for lymphomas diagnosed based on other tissue samples for 12 (48%) patients (MSGB – ). The clinical, biological, histological and radiological characteristics of both groups are reported in Table 1 . No major differences were found between groups for median ESSDAI at NHL diagnosis and the frequency of salivary gland hypermetabolism on PET-CT. MALT-type NHL was found in 24/25 (96%) patients including 13/13 (100%) of those MSGB + and 11/12 (92%) of those MSGB – . Six of the 13 (46%) MSGB + patients received no treatment, while all MSGB – patients were treated. Between diagnosis and 1 year of follow-up, ESSDAI scores without the NHL item did not differ (6.5 [3.5–9.5]) for the 6 untreated patients, but had significantly decreased for the 19 treated patients (3.5 [2.0–5.8]) (p=0.02). Conclusion: Our results showed that, when MALT lymphoma is suspected, MSGB contributed to diagnosing NHL, either at initial assessment or during pSS evolution, enabling MALT lymphoma diagnosis in at least a third of NHL patients and >50% when MSGB was obtained systematically. Thus, MSGB might avoid the need for a more invasive procedure. Moreover, our findings suggest MSGB should be obtained at pSS diagnosis, and repeatedly during follow-up, when NHL, especially MALT, is suspected. Disclosure of Interests: Simon Parreau: None declared, Raphaèle Seror Consultant of: BMS UCB Pfizer Roche, Benjamin Terrier: None declared, Barbara Burroni: None declared, Céline Jamart: None declared, Alexis Régent: None declared, Gaetane Nocturne: None declared, Luc Mouthon: None declared, Xavier Mariette Consultant of: BMS, Gilead, Medimmune, Novartis, Pfizer, Servier, UCB, Véronique LE GUERN Grant/research support from: UCB for GR2 study (to our institution)